Tuber borchii Shapes the Ectomycorrhizosphere Microbial Communities of Corylus avellana. Issue 2 (3rd April 2019) - Li, Xiaolin; Zhang, Xiaoping; Yang, Mei; Yan, Lijuan; Kang, Zongjing; Xiao, Yujun; Tang, Ping; Ye, Lei; Zhang, Bo; Zou, Jie; Liu, Chengyi
Abstract: In this study, eight-month-old ectomycorrhizae of Tuber borchii with Corylus avellana were synthesized to explore the influence of T. borchii colonization on the soil properties and the microbial communities associated with C. avellana during the early symbiotic stage. The results showed that the bacterial richness and diversity in the ectomycorrhizae were significantly higher than those in the control roots, whereas the fungal diversity was not changed in response to T. borchii colonization. Tuber was the dominant taxon (82.97%) in ectomycorrhizae. Some pathogenic fungi, including Ilyonectria and Podospora, and other competitive mycorrhizal fungi, such as Hymenochaete, had significantly lower abundance in the T. borchii inoculation treatment. It was found that the ectomycorrhizae of C. avellana contained some more abundant bacterial genera (e.g., Rhizobium, Pedomicrobium, Ilumatobacter, Streptomyces, and Geobacillus ) and fungal genera (e.g., Trechispora and Humicola ) than the control roots. The properties of rhizosphere soils were also changed by T. borchii colonization, like available nitrogen, available phosphorus and exchangeable magnesium, which indicated a feedback effect of mycorrhizal synthesis on soil properties. Overall, this work highlighted the interactions between the symbionts and the microbes present in the host, which shed light on our understanding of the ecological functions of T. borchii and facilitate its commercial cultivation.